(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article focuses on the education of today’s young generation, the formation of a scientific worldview in them by raising the culture of reading. There is also a culture of reading in the development of the moral requirements of the peoples of the East, such as morality, decency, courtesy, courtesy, respect for parents, teachers, politeness, openness, restraint, humility, commitment, honesty and so on. The importance of reading issues is analyzed in detail.